ULTRASOUND GUIDED FOAM SCLEROTHERAPY AS A PREFERRED TREATMENT OPTION FOR VARICOSE VEINS IN TERMS OF SAFETY, EFFICACY AND COST EFFECTIVENESS - Jamil, Muhammad; Usman, Rashid; Khan, Muhammad Irfan; Randhawa, Muhammad Afzal; Aman, Aaiza; Jamil, Areesha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the safety, efficacy and cost effectiveness of ultrasound-guided foam sclerotherapy in superficial venous reflux in Clinical, Etiological, Anatomical and Pathological (CEAP) classification grade 2-6 disease.Study Design: Retrospective observational study.Place and Duration of Study: Combined Military Hospital Rawalpindi, from Sep 2018 to Feb 2020.Methodology: One thousand and sixty-seven patients (1312 legs) with varicose veins were treated by ultrasound-guided foam sclerotherapy using 3% sodium tetradecyl sulphate for truncal veins and 1% for smaller veins in 1:4 ratio with air. After 7 days, leg was assessed clinically and radiologically with Duplex ultrasound for occlusion of veins and complications. Second, third and fourth sclerotherapy sessions were performed for residual/recurrence/new varicosities. Compression bandage was used for at least 3 months after treatment.Results: The overall eradication of superficial venous reflux and healing of ulcers, was seen in 92.1% (1208 legs). It was 83.5% (1095 legs) after 1st session of UGFS. Second, 3rd and 4th session of UGFS further increases this percentage of benefitted patients Deep vein thrombosis developed post procedure in 2 (0.18%) patients and pulmonary embolus in one patient. Three (0.28%) patients had transient visual disturbances within half an hour of treatment. Retreatment was required due to formation of new superficial venous reflux in 39 (2.9%) legs and recurrence in 93 (7.1%) legs.Conclusion: Ultrasound guided foam sclerotherapy is a better option of treatment in varicose veins in terms of safety, efficacy and cost effectiveness.